PENGARUH PENGGUNAA APLIKASI WORDWALL TERHADAP HASIL KETERAMPILAN MEMBACA SISWA KELAS IV DI SD ISLAM DATUK RIBANDANG - Sitti Nur Annisa Rahma; Tasrif Akib; Muhammad Saeful (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of using the Wordwall application on thereading skills of fourth-grade students at SD Islam Datuk Ribandang. The problem inthis study stems from the low interest and ability of students in understandingreading. This study uses a quantitative approach with a pre-experimental design typeone group pretest-posttest design. The subjects of the study were all 46 fourth-gradestudents. Data collection techniques used tests (pretest and posttest), observation,and documentation. The results of the descriptive analysis showed that the averagepretest score of students was 54.13, while the posttest score increased to 76.96. Theresults of the hypothesis test with the t-test showed that the significance value < 0.05,which means that there is a significant effect of using the Wordwall application onimproving students’ reading skills. Thus, the use of the Wordwall application as aninteractive learning media has proven effective in improving the reading skills offourth-grade students at SD Islam Datuk Ribandang.